Dysregulation of bladder corticotropin-releasing hormone receptor in the pathogenesis of human interstitial cystitis/bladder pain syndrome - Jhang, Jia-Fong; Birder, Lori A.; Jiang, Yuan-Hong; Hsu, Yung-Hsiang; Ho, Han-Chen; Kuo, Hann-Chorng (Scientific reports, 2019)
Stress is associated with exacerbated symptoms in patients with interstitial cystitis/bladder pain syndrome (IC/BPS). To investigate the mechanism of stress implicated on IC/BPS, we investigated expression of stress-response receptor corticotropin-releasing hormone receptor (CRHR) in bladder from IC/BPS patients. Twenty-three IC/BPS patients with Hunner’s lesion (HIC), 51 IC/BPS patients without Hunner’s lesion (NHIC), and 24 patients with stress urinary incontinence as controls were enrolled. Cystoscopic biopsies of bladder wall including mucosa and submucosa were obtained from all patients. Western blotting was used to investigate the bladder expression of the CRHR1 and CRHR2. Immunochemical staining revealed CRHR1 expression was mainly located in the submucosa while CRHR2 expression was mainly in uroepithelial cells. Compared to control subjects, the CRHR1 expression was significantly higher, while CRHR2 expression was significantly lower in IC/BPS patients. Further analysis of patients with HIC, NHIC, and control subjects showed that bladder in patients with HIC had significantly higher expressions of CRHR1 and significantly lower CRHR2. CRHR2 expression was significantly negatively correlated with O’Leary-Sant score and bladder pain. Our results indicate dysregulation of bladder CRHR1 and CRHR2 in patients with IC/BPS, and suggest CRH signaling may be associated with IC/BPS symptoms.